ESSENCE AND COMPONENTS OF HEALTH INSTITUTION MANAGEMENT DEVELOPMENT MANAGEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Introduction. One of the important current challenges in the field of health care is the formation of an effectivepersonnel policy to provide health care facilities with highly qualified medical workers and their continuousprofessional development, as the quality of medical services depends on it.The purpose of the article – to improve scientific approaches to determining the essence of staff developmentand its contentResults. The article summarizes the existing developments, identifies the dominant approaches to theinterpretation of the essence of staff development, namely: targeted, educational-oriented, professionally-oriented,personality-oriented, process, effective. It is established that staff development is a complex concept, has aninterdisciplinary nature, takes into account social, psychological, pedagogical, economic aspects. For the first time, athree-pronged approach was applied to determine the essence of the development of the organization's staff as aphenomenon, process, type of activity. As a phenomenon, the development of personnel of the organization isinterpreted as a dynamic open system, within which there is a change (improvement) of personal (intellectual,emotional, spiritual, moral, somatic), business and professional qualities of employees and their material, status underthe influence of internal and external factors. organization environment. The sign of dynamism determines theconsideration of the essence of staff development of the organization as a process, ie a set of stages and stages thatprovide the necessary personal, business and professional qualities of staff, which on the one hand, will qualitativelyperform responsibilities, tasks and functions. on the other hand, will ensure the interests of employees.Conclusiоns. The author's interpretation of the essence of personnel development expands the adaptivecapabilities of personnel management systems of organizations in accordance with the purpose and expected results,changes in the external and requirements of the institutional environment of health care.
Keywords: personnel, personnel development, personnel development management, health care institutions.